You have not given enough information to solve for x. The equation as you have described it is, 6(x+2) = ? That is not solvable as stated. If, however, you were to say, six times the total of 2 plus x equals zero, then we can solve for x. 6(x+2) = 0 6x + 12 = 0 6x = -12 x = -2
x2 + 2
-1
The following answer is based on the correct order of operations. If you meant something different, please alter the question accordingly. 5x+3x+2-3x+2x+1 7x+3
(14x)(x)+1 14x^2 + 1
You have not given enough information to solve for x. The equation as you have described it is, 6(x+2) = ? That is not solvable as stated. If, however, you were to say, six times the total of 2 plus x equals zero, then we can solve for x. 6(x+2) = 0 6x + 12 = 0 6x = -12 x = -2
x2 + 2
Why don't you figure it out yourself
-1
7
The following answer is based on the correct order of operations. If you meant something different, please alter the question accordingly. 5x+3x+2-3x+2x+1 7x+3
(14x)(x)+1 14x^2 + 1
depends on how question is wordedif (3 + 7) times (2 + 4)then 10 x 6 = 60also could be3 plus (7 x 2) plus 4 = 21or could be[(3 + 7) x 2] + 4 = 24
2 x 2 + 85 = 89
(-2)^4 = -2 x -2 x-2 x-2 = +16 ( a minus times a minus is plus)
x(x + 3) + 3(x + 3) = x2 + 3x + 3x + 9 = x2 + 6x + 9 = (x + 3)(x + 3) = (x + 3)2
2x2 + 9x + 10